2020
DOI: 10.1088/1475-7516/2020/03/048
|View full text |Cite
|
Sign up to set email alerts
|

Throwing away antimatter via neutrino oscillations during the reheating era

Abstract: The simplest possibility to explain the baryon asymmetry of the Universe is to assume that radiation is created asymmetrically between baryons and anti-baryons after the inflation. We propose a new mechanism of this kind where CP-violating flavor oscillations of left-handed leptons in the reheating era distribute the lepton asymmetries partially into the right-handed neutrinos while net asymmetry is not created. The asymmetry stored in the righthanded neutrinos is later washed out by the lepton number violatin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…We have shown that the matter-antimatter asymmetry of our Universe If the inflaton perturbatively decays also to lepton with flavor violation, the lepton asymmetry needs T R ≳ 10 8 GeV [1]. As recently shown in [2], if the reheating completes via the dissipation effect, where the scattering between the inflaton and the thermal plasma significantly generates the radiation, the reheating temperature can be even smaller. In particular, in the ALP inflation [14][15][16], ( In the low-scale ALP inflation, the abundance of the light scalar particles can be significantly altered due to the Bunch-Davies distribution formed during the inflation [17][18][19][20][21].…”
Section: Conclusion and Discussionmentioning
confidence: 52%
“…We have shown that the matter-antimatter asymmetry of our Universe If the inflaton perturbatively decays also to lepton with flavor violation, the lepton asymmetry needs T R ≳ 10 8 GeV [1]. As recently shown in [2], if the reheating completes via the dissipation effect, where the scattering between the inflaton and the thermal plasma significantly generates the radiation, the reheating temperature can be even smaller. In particular, in the ALP inflation [14][15][16], ( In the low-scale ALP inflation, the abundance of the light scalar particles can be significantly altered due to the Bunch-Davies distribution formed during the inflation [17][18][19][20][21].…”
Section: Conclusion and Discussionmentioning
confidence: 52%
“…To avoid the proton decays, one can introduce a Z 2 symmetry under which SM leptons are odd but the baryons are even or vise versa. In this case, the baryon asymmetry may be correctly obtained from neutrino oscillation with the higher dimensional term (3.24) [84,85] and also the quark oscillation could be important via the baryon-number-violating but baryon-parity-conserving operator [86]. Lastly, let us mention the confinement of SO(N ).…”
Section: 3 Cosmologymentioning
confidence: 93%
“…In the case of 1 TeV M 2 ≈ M 3 10 6 GeV, the right amount of baryon asymmetry may be generated via resonant leptogenesis [73,74], while vanilla leptogenesis [75] is difficult because of the low reheating temperature T R ∼ 10 6 GeV. When M 2,3 ∼ 1 -100 GeV, on the other hand, the baryon asymmetry may be obtained from flavor oscillations of the lefthanded leptons which are produced from the inflaton decays or scatterings [76,77]. If the ALP-lepton derivative couplings and y ν ij are flavor-violating, i.e.…”
Section: Jhep01(2021)152mentioning
confidence: 99%
“…This active lepton oscillation effect in the ALP inflation scenario was studied by solving kinetic equations for lepton density matrices in ref. [77]. It was found that the produced asymmetry is of the neutrino Yukawa matrix squared, O((y ν ) 2 ), at the leading order, since the leptons can be efficiently produced from the ALP-lepton interaction that is assumed to be flavor-violating, and the tuning between M 1 and M 2 is not needed.…”
Section: Jhep01(2021)152mentioning
confidence: 99%